Community Empowerment Strategy in Business Capacity Development Program of PT. Permodalan Nasional Madani - YR. Wijayandaru; Wilfridus B. Elu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses the impact of the COVID-19 pandemic on the MSME sector in Indonesia and the role of PT Permodalan Nasional Madani (PT. PNM) in facilitating the growth and empowerment of Micro, Small and Medium Enterprises (MSMEs). This pandemic has changed the landscape of the economy and society globally. MSMEs have a crucial role in economic growth and employment in Indonesia. PT PNM, as a financial institution that focuses on empowering less prosperous communities, provides financing, mentoring and training to MSMEs. PT PNM is a financial institution that focuses on empowering underprivileged communities through access to capital, mentoring and training. The PKU Division provides assistance and training to customers, especially in dealing with marketing challenges during the pandemic. This study analyzes the MSME empowerment strategy through the ACTORS theory approach and identifies success factors that contribute to the national economy. With this support, MSMEs are expected to recover and contribute more to Indonesia's economic recovery. The research uses a qualitative approach with primary data from interviews with EVP PNM, Head of PKU Division, business actors. Secondary data: PNM documents, books, articles